2023
DOI: 10.3390/jcm12206623
|View full text |Cite
|
Sign up to set email alerts
|

Proprioception and Mechanoreceptors in Osteoarthritis: A Systematic Literature Review

Francesca Salamanna,
Silvio Caravelli,
Laura Marchese
et al.

Abstract: Purpose: Osteoarthritis (OA) is one of the most common chronic diseases in the world. It is frequently accompanied by high levels of persistent pain, as well as substantial impairments in function and functional capacity. This review aims to systematically analyze the changes in proprioception and related mechanoreceptors in OA patients. Methods: Studies from September 2013 to September 2023 were identified by conducting searches on the PubMed, Web of Science, and Scopus electronic databases following the PRIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Although previous studies have found no significant correlation in proprioception scores between the ankle and knee joins ( Han et al, 2013a ; Han et al, 2013b ), the ankle proprioception impairment detected in the KOA cohort may be ascribed to a central mechanism resulting from KOA. Research has suggested that KOA may cause loss of mechanoreceptors, e.g., Golgi corpuscles, Ruffini corpuscles, and fusimotor hyperactivity abnormally induced by nociceptive stimulation, which contribute to peripheral impairments on joint position sense and movement sense in the affected knee joint ( Salamanna et al, 2023 ). No recent ankle injury history or ankle OA existed in the recruited KOA cohort in this study, indicating a possible altered central processing on neuromuscular control in the lower limb may exist in the KOA cohort.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although previous studies have found no significant correlation in proprioception scores between the ankle and knee joins ( Han et al, 2013a ; Han et al, 2013b ), the ankle proprioception impairment detected in the KOA cohort may be ascribed to a central mechanism resulting from KOA. Research has suggested that KOA may cause loss of mechanoreceptors, e.g., Golgi corpuscles, Ruffini corpuscles, and fusimotor hyperactivity abnormally induced by nociceptive stimulation, which contribute to peripheral impairments on joint position sense and movement sense in the affected knee joint ( Salamanna et al, 2023 ). No recent ankle injury history or ankle OA existed in the recruited KOA cohort in this study, indicating a possible altered central processing on neuromuscular control in the lower limb may exist in the KOA cohort.…”
Section: Discussionmentioning
confidence: 99%
“…First, most of the studies have focused on proprioception at the knee only, so little is known about the proprioceptive acuity of other lower limb joints, such as the ankle, or about their role during normal function ( Salamanna et al, 2023 ). Although it seems logical to investigate the capability of the “affected” joint, i.e., the knee, to achieve successful movement control in normal function, the brain has to integrate proprioceptive information from multiple joints in the kinetic chain ( Han et al, 2016a ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Osteoarthritis (OA) of the hip is a prevalent degenerative joint disease that significantly impacts the musculoskeletal system, leading to pain, disability, and a diminished quality of life [1,2]. The pathophysiology of hip OA involves not only the cartilaginous wear and changes in bone structure but also extends to muscular weakness, proprioceptive deficits, and balance impairments [3,4]. These factors contribute to the complexity of the condition and the challenge it poses to clinical management [4].…”
Section: Introductionmentioning
confidence: 99%
“…The pathophysiology of hip OA involves not only the cartilaginous wear and changes in bone structure but also extends to muscular weakness, proprioceptive deficits, and balance impairments [3,4]. These factors contribute to the complexity of the condition and the challenge it poses to clinical management [4].…”
Section: Introductionmentioning
confidence: 99%